Termer i text - Ett datorstött övningsmaterial för termhantering - Lange, Sven; Merlin, Lars (Nordiske Studier i Leksikografi, 1997)
Terminologica/ Playground isa computer aided material for creation ofterms withln fictive worlds. It is a complement to theoretical studies in university programs for translators and technical writers. We regard terms as an important part of texts, rather than conceptional units. Shortness and morfological flexibility is of great value. Our material is based on the function Linked text in Word for Windows 6.0. The Terminological Playground displays the principles for word creation. To evaluate the survival potential ofthe new words we compare their qualities with the opposite, lexical death.